FIXED ORTHODONTIC APPLIANCES – THE RISK FACTOR OF DENTAL HARD TISSUES AND PERIODONTAL TISSUES DISEASES DEVELOPMENT - P.S. Flis; O.V. Savychuk; H.V. Novakovska; O.O. Opanasenko; Yu.P. Nemyrovych; О.K. Novakovska (Український стоматологічний альманах)
Purpose: To improve the quality of prevention and treatment of disease of dental hard tissues and periodontal tissues in orthodontic patients. Materials and methods: 80 orthodontic patients aged from 13 to 21 were examined. Results: Up-to-date measures of treatment and prevention were developed. Conclusions: This approach guarantees the treatment, that increases the level of oral health of the patients.